Tomaševska problēma - Danemane, Kristīne (Latvijas Universitāte, 2008)
Bakalaura darbā aplūkota Tomaševska problēma par noteikta veida vienības vektoru skaitu Eiklīda n - dimensiju telpā R. Darbā iegūts tās atrisinājums, ja n = 2, 3, 4, 5, 6.

Tomaszewski's problem about the number of certain type of unit vectors in n dimensional space R has been considered in this bachelor's work. The solution has been obtained for n = 2, 3, 4, 5, 6.
Tomaszewski's problem
Keywords: Matemātika